Impact of Covid-19 Pandemic School Close Down on the Research Programme of Higher Institutions - Ogunode Niyi Jacob (International Journal of Advances in Data and Information Systems, 2020)
The purpose of this study is to examine the impact of covid-19 pandemic school close down on the research programme of higher institutions in Abuja, Nigeria. Descriptive survey design was used for the study and 4 research questions was developed for the study. Random sampling method was used to select 120 researchers in the four sampled institutions. The instrument used for collection of data was a structured questionnaire. Result collected revealed that 100% of the respondents agreed that Covid-19 pandemic school closure have impact on research program of higher institutions in FCT, 100% of the respondents agreed that Covid-19 pandemic will affects the flow of international research grants into higher institutions in FCT, 92% of the respondents agreed that Covid-19 pandemic will affects government funding of research higher institutions in FCT and 100% agreed that higher institutions as part of their community services by creating awereness to the general public on prevention of covid-19.The study also showed that 100% of the respondents agreed that higher institutions in Federal Capital Territory are collaborating with other institutions on the research for covid-19 vaccine while 69.17% of the respondents agreed that higher institutions in FCT are producing face masks for free distributions for the people to protect them from containing the covid-19 in Abuja. Based on this finding, this paper thereby recommends that government should increase the funding of research programme in Abuja and other higher institutions in the country.